The Effects of Government Interventions in the Financial Sector on Banking Competition and the Evolution of Zombie Banks - Calderon, Cesar; Schaeck, Klaus (Journal of Financial and Quantitative Analysis, 2016)
We investigate how government interventions such as blanket guarantees, liquidity support, recapitalizations, and nationalizations affect banking competition. These issues are critical for stability, access to finance, and economic growth. Exploiting cross-country and cross-time variation in the timing of interventions and accounting for their nonrandomness, we document that liquidity support, recapitalizations, and nationalizations trigger large increases in competition. We also find some more nuanced evidence that zombie banks’ market shares in crisis countries evolve together with interventions. A higher frequency of interventions coincides with greater zombie bank presence, and increases in competition are larger when zombie banks occupy bigger market shares.